Characterization of Clay from Merauke Regency and Its Utilization as an Adsorbent of Free Fatty Acids in the Purification of Waste Cooking Oil - Muhammad Rasyiid Maulana; John Yoro Parlindungan; Abraham Laurens Rettob; Lamtiar Ferawaty Siregar; Hendro Hitijahubessy (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
This study investigates the characterization and application of natural clay from Merauke as an adsorbent for the purification of waste cooking oil. The clay was characterized using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) before and after acid activation. XRD analysis revealed quartz as the dominant mineral, while acid activation caused partial dissolution of layered silicates, leading to structural modifications without affecting quartz stability. SEM images confirmed morphological changes from compact aggregates with limited pores to rougher surfaces with larger and more interconnected pores, indicating increased surface area and porosity. Adsorption experiments demonstrated that both natural and acid-activated clays reduced free fatty acids (FFA) in waste cooking oil, with the acid-activated clay consistently showing higher efficiency. Prolonged stirring times (1, 3, and 5 hours) further enhanced adsorption, though the reduction rate decreased over time as adsorption sites approached saturation. In addition to lowering FFA levels, the treatment improved the visual quality of the oil by reducing discoloration. These findings highlight that acid-activated clay from Merauke possesses promising potential as a low-cost and effective adsorbent for oil purification and broader environmental remediation applications.